2021
DOI: 10.1007/s00415-021-10780-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mRNA vaccination leading to CNS inflammation: a case series

Abstract: The availability of vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), provides hope towards mitigation of the coronavirus disease 2019 (COVID-19) pandemic. Vaccine safety and efficacy has not been established in individuals with chronic autoimmune diseases such as multiple sclerosis (MS). Anecdotal reports suggest that the vaccines may be associated with brain, spinal cord, peripheral nervous system, and cardiac inflammation. Based on the high morbidity and unpredictable course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 73 publications
1
99
0
Order By: Relevance
“…In the presented cases, there was no family history of neurologic and systemic autoimmune diseases or personal and family history of vaccine related adverse events. Similar to our findings, there are reports of myelitis in the setting of recent exposure to COVID-19 vaccines ( Khayat-Khoei et al, 2021 ; Havla et al, 2021 ) and cases of unmasked multiple sclerosis following administration of ChAdOx1 nCoV-19 vaccine ( Voysey et al, 2021 ). Although lack of a control cohort makes establishing causation difficult, the temporal relationship between vaccine administrations may suggest the inflammatory reaction to the vaccine might have triggered a first clinical event in individuals with pre-clinical MS. Alternatively the occurrence of these cases may represent a spurious association given a combination of a common event, namely vaccination with mRNA COVID-19 vaccines (currently at 56.2% of the Ohio population as reported on www.coronavirus.ohio.gov ), and MS as a neurological disease with relatively common incidence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the presented cases, there was no family history of neurologic and systemic autoimmune diseases or personal and family history of vaccine related adverse events. Similar to our findings, there are reports of myelitis in the setting of recent exposure to COVID-19 vaccines ( Khayat-Khoei et al, 2021 ; Havla et al, 2021 ) and cases of unmasked multiple sclerosis following administration of ChAdOx1 nCoV-19 vaccine ( Voysey et al, 2021 ). Although lack of a control cohort makes establishing causation difficult, the temporal relationship between vaccine administrations may suggest the inflammatory reaction to the vaccine might have triggered a first clinical event in individuals with pre-clinical MS. Alternatively the occurrence of these cases may represent a spurious association given a combination of a common event, namely vaccination with mRNA COVID-19 vaccines (currently at 56.2% of the Ohio population as reported on www.coronavirus.ohio.gov ), and MS as a neurological disease with relatively common incidence.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from evidence that the yellow fever vaccine may be associated with relapses, other vaccine data does not support an association between vaccination and MS relapse risk ( Zrzavy et al, 2019 ; Mailand and Frederiksen, 2017 ). There have been four cases of new MS diagnoses following mRNA COVID-19 vaccine administration, but MRI studies, in those cases demonstrated a mix of old and new lesions, which prompted the authors to conclude there likely was clinically latent disease prior to vaccination itself ( Khayat-Khoei et al, 2021 ; Havla et al, 2021 ; Fujimori et al, 2021 ). Both Pfizer-BioNTech and Moderna vaccines against COVID-19 are highly effective mRNA vaccines approved by FDA ( Banerji et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, neurological involvements have been reported after vaccinations (Fenichel 1982 ). In COVID-19 vaccinations, although neurological complications including bell’s palsy, Guillain-Barré syndrome, transverse myelitis, and multiple sclerosis have been observed, the incidence is not well known (Wan et al 2021 ; Havla et al 2021 ; Khayat-Khoei et al 2021 ). Herein, we report a patient with trigeminal neuritis following the vaccination, incidentally treated with steroid.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors underlined that in their case series there was no background knowledge of the amount of patients who underwent vaccination in the same period. Moreover, they did not perform comparisons with the rate of relapse among patients who did not receive COVID-19 vaccination [15]. In our MS center, with over more than 300 individuals with MS who underwent COVID-19 vaccination, we observed only one possible disease relapse occurring during the month following vaccination.…”
Section: Discussionmentioning
confidence: 88%